Pelatihan Penelitian Tindakan Kelas (PTK) untuk Pemberdayaan Guru di MTs Huffadh Al-Itqoniyyah - Nur'aini Muhassanah; Asfi Ainuranti (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
The purpose of this training activity is to improve the ability of teachers to prepare Classroom Action Research (CAR) proposals. Classroom action research is thus one of the abilities that must be possessed by teachers to maintain the professionalism of their performance. The training participants were Mts and MA Huffadh Al-Itqoniyyah teachers, totaling 25 people divided into 5 groups. This training is scheduled in two activities. The first activity is the delivery of material related to the preparation of class action research proposals which is carried out offline once. While the second activity is assisting training participants in preparing class action research proposals which are carried out online through the WA Group, Zoom, and GMeet. The results of this activity are in the form of output proposals, where 60% of the training participants are able to complete the assignments or the output of the training is in the form of class action research proposals. Meanwhile, 40% of the participants could not complete the output due to limited time and busyness of the participants. Of the 3 PTK proposals that were the outputs of this activity, 2 proposals were assessed with good criteria and 1 proposal with very good criteria.